2022
DOI: 10.1155/2022/4036030
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Evaluation Method of Elderly Family Medical Product Design Based on AHP

Abstract: Due to the needs of an aging society, household medical products for the elderly are becoming increasingly important in everyday life. To improve the quality and scientificity of household medical product design for the elderly, this study uses the analytic hierarchy process to improve the evaluation method of household medical product design for the elderly and to promote the vigorous development of household medical products for the elderly. Based on previous research, firstly, this paper summarised the desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…When CR ≤ 0.1, the result of the hierarchical total ordering is considered to be consistent with the consistency judgment; otherwise, the judgment matrix needs to be adjusted or reconstructed until the total ordering meets the consistency judgment. Table 3 is reproduced from the study by Yue et al [26].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…When CR ≤ 0.1, the result of the hierarchical total ordering is considered to be consistent with the consistency judgment; otherwise, the judgment matrix needs to be adjusted or reconstructed until the total ordering meets the consistency judgment. Table 3 is reproduced from the study by Yue et al [26].…”
Section: Methodsmentioning
confidence: 99%
“…Some scholars have also applied different quantitative methods to product innovation design or product evaluation in the last two years. Oey et al [23] sought a way to accommodate user requirements in their product and process improvement, Lu et al [24] constructed a product form evolution design method integrating the TRIZ contradiction matrix to simplify the product form evolution process, Liu et al [25] proposed a conceptual design evaluation method based on Z-numbers, Yue et al [26] improved the evaluation system of the design of household medical products for the elderly, Zhang et al [27] proposed a lead user identification method based on user behavior data and contribution content analysis, Wang et al [28] proposed a product evaluation method that combines natural language processing techniques and fuzzy multicriteria decision-making, and Wurster et al [29] used consumers as a valuable source of information to specify features of the output of an innovative CE ecosystem. e overall comparison between this article and previous studies is shown in Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…Te sorted ambulance requirements are divided into three layers, that is, target layer, principle layer, and element layer. Te product design goal-"ambulance design"-is set as the target layer, denoted by the letter A. Diferent demand categories-" transportation," "medical aid," and "body appearance"-are set as the principle layer, which are represented by B1, B2, and B3, respectively [20]. 14 kinds of user demands including "quick departure at any time," "not afected by congestion," "through the narrow roads of the community," "timely arrival at the scene," "stable and safe driving," "emergency rescue function," "medical transport function," "intensive care function."…”
Section: Analytic Hierarchy Process For Sequencing Ambulance Demandsmentioning
confidence: 99%
“…Their approach, validated through stakeholder participation, effectively translated complex customer requirements into specific design elements. Han [13] et al used a survey to delineate design elements for medical products in elderly households, applying an AHP model for systematic prioritization. This research enhances medical product design evaluation for elderly usage.…”
Section: Introductionmentioning
confidence: 99%